Delivering nitric oxide with nanoparticles - Quinn, John F.; Whittaker, Michael R.; Davis, Thomas P. (Journal of controlled release, 2015)
While best known for its important signalling functions in human physiology, nitric oxide is also of considerable therapeutic interest. As such, nanoparticle-based systems which enable the sustained exogenous delivery of nitric oxide have been the subject of considerable investigation in recent years. Herein we review the various nanoparticle systems that have been used to date for nitric oxide delivery, and explore the array of potential therapeutic applications that have been reported. Specifically, we discuss the modification of sol–gel based silica particles, functionalised metal/metal oxide nanoparticles, polymer-coated metal nanoparticles, dendrimers, micelles and star polymers to impart nitric oxide release capability. We also consider the various areas in which therapeutic applications are envisaged: wound healing, antimicrobial applications, cardiovascular treatments, sexual medicine and cancer treatment. Finally, we discuss possible future directions for this versatile and potentially important technology. [Display omitted]